Globalization, nationalism, and clearing systems - Jan A. Kregel (Levy Economics Institute of Bard College, 2019)
As global market integration collides with growing demands for national political sovereignty, Senior Scholar Jan Kregel contrasts two diametrically opposed approaches to managing the tensions between international financial coordination and national autonomy. The first, a road not taken, is John Maynard Keynes's proposal to reform the postwar international financial system. The second is the approach taken in the establishment of the eurozone and the development of its settlement and payment system. Analysis of Keynes's clearing union proposal and its underlying theoretical approach highlights the flaws of the current eurozone setup.
Keywords: 330